Crushing of vertex-based hierarchical honeycombs with triangular substructures. (January 2020) - Zhang, Dahai; Fei, Qingguo; Liu, Jingze; Jiang, Dong; Li, Yanbin
Abstract: Triangular lattices were hierarchically incorporated into a regular hexagonal honeycomb to substitute each vertex of the regular honeycomb. To investigate the crushing behaviors of the newly constructed vertex-based hierarchical honeycombs, finite element (FE) analyses were carried out subsequently for both in-plane and out-of-plane crushing. Effect of the hierarchical organizational parameter on deformation mode, crushing response and energy absorption capacity were discussed respectively. The results showed that the hierarchy significantly affected the crushing behaviors of the honeycomb differently for in-plane and out-of-plane crushing. The hierarchy had a far greater influence on the deformation mode for in-plane crushing than out-of-plane crushing. Compared with that of the regular honeycomb, hierarchy not always improved the honeycomb in terms of plateau stress and specific energy absorption ( SEA ). The maximum plateau stress and SEA of the hierarchical honeycombs increased by up to approximately 127% and 109% respectively under crushing along L direction (in-plane ribbon direction); 122% and 108% respectively under crushing along W direction (in-plane width direction); and 30% and 34% respectively under crushing along T direction (out-of-plane direction). Highlights: A novel type of vertex-based hierarchical honeycombs with triangular substructures was introduced. Hierarchy significantly affected the crushing behaviors for in-plane and out-of-plane crushing differently. Hierarchy not always improved the honeycombs in terms of plateau stress and energy absorption capacity. The maximum improvement of crashworthiness performed much better for in-plane crushing than out-of-plane crushing.